The Future of Our Country is in the Hands of Youth - Shodiyev Alisher; Hojiev Sherali (Research Parks Publishing LLC, 2020)
In the period of rapid development, the comprehensive development of the country depends on the intellectual potential of its population. In today's globalized world, the perspective of an intellectually underdeveloped state is unilateral. . The attitude of our people to the processes of globalization can be explained by the well-known Indian scientist Mahatma Gandhi: ”I cannot always close my home gates and windows, because my house needs fresh air. At the same time, I do not want the air coming through our doors and windows to turn into a storm, to destroy my house, and to destroy myself”.